The level of glycemia as a risk factor of cardiovascular diseases - Ashot Musaelovich Mkrtumyan (Сахарный диабет)
The paper deals with the main aspects of pathogenesis of cardiovascular diseases in patients with disturbed carbohydrate metabolism. Results of theADVANCE study are presented that confirm the importance of intensive control of glycemia for the reduction of the overall risk of diabetic complicationsand death from cardiovascular pathology.